INTELLIGENT BUILDING SYSTEM: A STUDY ON EVALUATION OF INFLUENCING FACTORS FOR SUSTAINABLE DEVELOPMENT IN PRIVATE UNIVERSITIES IN KLANG VALLEY - Mahazir, Mashanim; Loo, Ji Yung; Mohd Nasir, Mohd Farhan; Elmi, Noor Hidayah; Chia, Eunice Chia Mei Ling (Journal of Engineering & Technological Advances, 2022)
This project is carried out to study the evaluation of influencing factors for sustainable development with intelligent building systems in private universities in Klang Valley. An intelligent building system can be defined as a building automation system that is integrated into the physical plant and building facilities and linked with the corporate systems to ensure the building management system can be brought up to date on the building operating cost, and energy efficiencies of the building. Questionnaire surveys were distributed to collect the data. Descriptive analyses were used to analyse the data using Statistical Package for Social Science (SPSS). The study showed that the main barriers to implementing Intelligence Building System (IBS) were the high initial cost. The benefits of using IBS were reduced waste, pollution, and environmental degradation. The potential chances in implementing IBS were using sustainable building materials, and recycling and reuse of materials. The ways to deal with these issues are to learn, understand, and accept, then apply the intelligent building system in the campus and try to keep up with the latest technology and innovation to increase the quality of life and productivity of the people like lecturers, students, admin staffs who are using the campus every day.